Rutin, A Natural Inhibitor of IGPD Protein, Partially Inhibits Biofilm Formation in Staphylococcus xylosus ATCC700404 in vitro and in vivo - Qu, Qianwei; Cui, Wenqiang; Xing, Xiaoxu; Zou, Rongfeng; Huang, Xingyu; Wang, Xiaozhen; Wu, Tong; Bello-Onaghise, God’spower; Yuan, Shuguang; Li, Yanhua (Frontiers in Pharmacology, 2021)
Staphylococcus xylosus (S. xylosus) has become an emerging opportunistic pathogen due to its strong biofilm formation ability. Simultaneously, the biofilm of bacteria plays an important role in antibiotic resistance and chronic infection. Here, we confirmed that rutin can effectively inhibit biofilm formation in S. xylosus, of which the inhibition mechanism involves its ability to interact with imidazolyl phosphate dehydratase (IGPD), a key enzyme in the process of biofilm formation. We designed experiments to target IGPD and inhibited its activities against S. xylosus. Our results indicated that the activity of IGPD and the amount of histidine decreased significantly under the condition of 0.8 mg/mL rutin. Moreover, the expression of IGPD mRNA (hisB) and IGPD protein was significantly down-regulated. Meanwhile, the results from molecular dynamic simulation and BLI technique showed that rutin could bind to IGPD strongly. Additionally, in vivo studies demonstrated that rutin treatment reduced inflammation and protect mice from acute mastitis caused by S. xylosus. In summary, our findings provide new insights into the treatment of biofilm mediated persistent infections and chronic bacterial infections. It could be helpful to design next generation antibiotics to against resistant bacteria.